Planteome: A resource for common reference ontologies and applications for plant biology - Jaiswal, P.; Cooper, Laurel D.; Elser, J.L.; Meier, A.; Laporte, Marie-Angélique; Mungall, C.; Smith, B.; Johnson, E.K.S.; Seymour, M.; Preece, J.; Xu, X.; Kitchen, R.S.; et al. (2016)
Around the world, a small number of plant species serve as the primary source of food for the human population, yet these crops are vulnerable to multiple stressors, such as diseases, nutrient deficiencies and unfavorable environmental conditions. Traditional breeding methods for plant improvement may be combined with next-generation methods such as automated scoring of traits and phenotypes to develop improved varieties. Linking these analyses to the growing corpus of genomics data generated by high-throughput sequencing, transcriptomics, proteomics, phenomics and genome annotation projects requires common, interoperable, reference vocabularies (ontologies) for the description of the data. The Planteome initiative (www.planteome.org) is developing the needed suite of common reference ontologies that describe anatomy and development in Plant Ontology (PO), Plant Trait Ontology (TO), and Plant Environment Ontology (EO) and the Plant Stress Ontology (PSO) for describing the abiotic and biotic stresses. The project will also host ontologies such as Gene Ontology (GO), Chemical Entities of Biological Interest (ChEBI), Protein Ontology (PRO) and the Phenotypic Qualities Ontology (PATO) developed by collaborators. The project database and the online resources will provide researchers tools to search and browse and remote access via APIs for semantic integration in annotation tools and data repositories providing resources for plant traits, phenotypes, diseases, genomes, gene expression and genetic diversity data across a wide range of plant species.